Vitamin D and mental health during the Covid-19 outbreak - Oliveira, Séphora Natércia Albuquerque; Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
The relationship between hypovitaminosis D and depressive disorder is well documented in the medical literature. However, the biological mechanisms by which vitamin D can modulate psychological distress are still unclear. Containment measures can decrease individual’s exposure to the sun, significantly increasing their needs for vitamin D, a nutrient already deficient in patients with depression. Therefore, it can be inferred that by ingesting the same amount of vitamin D, depressive individuals seem to obtain a lesser amount of this nutrient from the sun’s rays when compared to healthy people. We found the relationship between vitamin D and COVID-19 has been increasingly studied, mainly due to the changes that this substance can cause in the inflammatory process - especially in the release of cytokines, in SARS and in lung injuries. Despite the benefits, the existing observational studies on this exchange are not enough to definitively associate vitamin D as a protective factor for COVID-19.